Implementasi Undang-undang Nomor 38 Tahun 1999 tentang Pengelolaan Zakat - Jihad, Nur (Jurnal Hukum IUS QUIA IUSTUM, 2018)
The rapid ofindustrious and economical development as a enterpreunership need the solution of calculation and charge of tax obligation in orderthat the ommision of poverty caused byeconomical recession cab be improved. Itremembers thatthe management oftithe (zakat) in theoldIslamicJurisprudence isstill limited, while thelevel ofcomplexity because of economical development is very multl demensiona. This article is going to see deeplyhow Is implementation of regulation number 38 year of 1999 about tithe (zakat) management operationally. Is itsignificant asndeffective enough or it faces the handicaps and other problem in which it needs solution.